Remarks to the Spring Meetings 2021 Development Committee - Malpass, David (Washington, DC: World Bank, 2021)
World Bank Group President David Malpass spoke about how the Development Committee plays an essential and unique role in the international cooperation architecture. He highlighted the actions taken by World Bank to respond quickly to the Coronavirus (COVID-19) pandemic, which includes new COVID-related emergency health programs in 112 countries, vaccination operations that are expected to reach four billion dollars in commitments available in fifty countries by mid-year, and a quick doubling of trade and working capital finance to help fill the banking vacuum that hit private sectors. He urged all to consider how we can restore growth in developing countries and help reverse the growing inequality, in terms of access to vaccinations, unsustainable debt, and adverse climate impacts. He was very pleased with the G20’s endorsement of advancing the IDA replenishment cycle to 2021. He mentioned that the main elements of the World Bank Group’s Climate Change Action Plan were presented last week. He discussed the three topics of Debt, Coronavirus (COVID-19) Vaccines, and Green Resilient and Inclusive Development which are critical to a sustainable recovery. He concluded we can generate a recovery that ensures a broad and lasting rise in prosperity, especially for the poorest and most vulnerable.